2020
DOI: 10.21109/kesmas.v15i3.3296
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Indicators and C-reactive Protein in Indonesian Adults (≥ 40 years): The Indonesian Family Life Survey-5 2014–2015

Abstract: C-reactive protein (CRP) is the best clinical marker for systemic inflammation. Obesity is associated with increased CRP levels. Systemic inflammation is present before morbidity occurs. Research reveals that the identification of obesity indicators and CRP levels is limited among Indonesians. The present study investigated the associations between obesity indicators (body mass index [BMI], waist circumference [WC], waist-to-hip ratio [WHR], waist-to-height ratio [WHtR]) and CRP levels among Indonesian adults.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The different results compared with those of the present study might be caused by different research models. Mahwati et al (11) adjusted the effect of social variables including marital status, education, and residence in the analysis while the present study measured the effect of several obesity indices, age, and blood pressure on hsCRP levels. In our study, age and diastolic blood pressure showed no significant association with hsCRP levels, and after multiple linear regression analysis, BMI was a consistent indicator associated with hsCRP.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The different results compared with those of the present study might be caused by different research models. Mahwati et al (11) adjusted the effect of social variables including marital status, education, and residence in the analysis while the present study measured the effect of several obesity indices, age, and blood pressure on hsCRP levels. In our study, age and diastolic blood pressure showed no significant association with hsCRP levels, and after multiple linear regression analysis, BMI was a consistent indicator associated with hsCRP.…”
Section: Discussionmentioning
confidence: 94%
“…A significant correlation between BMI and hsCRP levels was also found in obese children and adolescents. (14) On the other hand, Mahwati et al, (11) after performing logistic regression, reported a significant association of WHR and WHtR with hsCRP, but no association was observed of BMI and WC with hsCRP. The different results compared with those of the present study might be caused by different research models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In addition, Interleukin-6 has been reported as a cytokine with pleiotropic effects on inflammation, 23 immune response and haematopoiesis. 24 Furthermore, Interleukin-6 can also stimulate the production of several acute phase reactants such as C-Reactive Protein and stimulate hepatic lipogenesis associated with obesity 25 and insulin resistance. 26 However, the limitation of this study is that it was extremely difficult to properly the arrange the eating schedules for both groups of the type 2 diabetes mellitus patients hence, this could have affected the outcomes of the research findings.…”
Section: Resultsmentioning
confidence: 99%